2000
DOI: 10.1139/t99-120
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductivity of bentonite-sand mixtures

Abstract: The use of bentonite alone or amended with natural soils for construction of liners for water-retention and waste-containment facilities is very common. The importance of bentonite content in reducing the hydraulic conductivity of liners is well recognised. The study illustrates the role of the size of the coarser fraction in controlling the hydraulic conductivity of the clay liner. It has been shown that at low bentonite contents the hydraulic conductivity of the liner varies depending on the size of the coar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(72 citation statements)
references
References 11 publications
3
63
0
6
Order By: Relevance
“…Although the compacted clay soils have many superiorities like low permeability (< 10 −9 m/s), they have instability problems because of their potential of high shrinkage and expansion [22,23,24]. According to the design criteria of Turkish Solid Waste Management Legislation, the liner component is compacted to provide a hydraulic conductivity no greater than 10 −9 m/s [25]. The composition of leachates changes over time due to the evolution process of waste degradation which is strongly linked to the mechanical-chemical and biological reaction taking place in the land ill [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the compacted clay soils have many superiorities like low permeability (< 10 −9 m/s), they have instability problems because of their potential of high shrinkage and expansion [22,23,24]. According to the design criteria of Turkish Solid Waste Management Legislation, the liner component is compacted to provide a hydraulic conductivity no greater than 10 −9 m/s [25]. The composition of leachates changes over time due to the evolution process of waste degradation which is strongly linked to the mechanical-chemical and biological reaction taking place in the land ill [1].…”
Section: Introductionmentioning
confidence: 99%
“…The clay soils in the land ills may cause an increase in hydraulic conductivity over time due to water pressure [21]. Sivapullaiah et al [25,26] determined that the permeability of soils decreases with increasing content of smaller particles.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed experimentally that soil hydraulic conductivity depends, among others, on its particle size distribution and specific surface area as well as on void ratio, swelling and ion exchange capabilities (Alamgir et al, 2005;Baumann, 1999;Benson & Trast, 1995;Egloffstein, 2001;Foged & Baumann 1999;Mitchell & Jaber 1990;Vukovic & Soro, 1992). Hydraulic conductivity usually decreases with the increase of the content of fine particles (Alamgir et al, 2005;Sivapullaiah et al, 2000), as shown in Fig. 1.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…According to reported numerous studies (e.g. Mitchell & Jaber, 1990, Sivapullaiah 2000Schmitz 2006) evaluating soil and liquid properties controlling the saturated hydraulic conductivity in liners, hydraulic conductivity decreases along with increased content of fine particles. The increased mechanical stress observed in compacted soils results in reduction of electrical forces effect on soil behavior but the soil fabric is affected by the chemical properties of the flowing liquid (Mitchell & Soga, 2005).…”
Section: Influence Of Leachates On Water Permeabilitymentioning
confidence: 99%
“…Typically, the hydraulic conductivity of compacted clay should be less than 1x10 -7 cm/s for soil liners and covers [4], [5]. The required liner thickness for domestic and light industrial waste types as suggested by [5] is to be 0.6 m for compacted clay liners.…”
Section: Introductionmentioning
confidence: 99%